Discrete time H∞ synthesis conditions for LPV filter design. Issue 26 (2018) - Pandey, Amit; de Oliveira, Maurício C.
Abstract: We are interested in H ∞ synthesis conditions for Linear Parameter Varying (LPV) filter design. We prove that an existing class of sufficient conditions for poly-quadratic H ∞ filter synthesis is in fact necessary as well. We develop alternative conditions based on a new theory of duality for poly-quadratic Lyapunov functions. We use these results to show how poly-quadratic H ∞ state feedback synthesis conditions can be used for poly-quadratic H ∞ LPV filter synthesis.